Analysis of Bigetron E-Sport Team Branding Strategy via the Instagram Platform - Alfin Imam Mahsus; Poppy Febriana (Jurnal Spektrum Komunikasi, 2024)
This research aims to analyze the branding strategy used by the Bigetron E-Sport Team via the Instagram platform, with a focus on symbolic aspects of strategy, brand as a friend, nostalgia and event branding. The research method used is descriptive qualitative with data collection through non-participant observation of feed posts and reels from the @bigetronesports account. The theory used in this research refers to branding strategy concepts in the book "Strategic Brand Management". The results obtained from this research are that the Bigetron E-Sport Team has succeeded in implementing an adaptive, idealistic and differentiated branding strategy through the Instagram platform. They utilize symbols such as the color red and silhouette images to build a strong brand identity and attract fans' attention. Apart from that, the Bigetron E-Sport Team also uses Event Branding as part of their branding strategy, by holding offline events to increase brand visibility, attract media attention, and introduce players and sponsors to fans. By selecting these aspects, this research provides a deeper understanding of how the Bigetron E-Sport Team utilizes branding strategies through the Instagram platform to strengthen brand identity, deepen relationships with fans, and increase their presence in the E-Sport industry. It is hoped that this research will provide valuable insight for branding practitioners and E-Sport fans in understanding effective branding strategies in the context of social media.